A Window for Enhanced Oral Delivery of Therapeutics via Lipid Nanoparticles - Amekyeh H; Sabra R; Billa N (Dove Medical Press, 2024)
Hilda Amekyeh,1 Rayan Sabra,2 Nashiru Billa3 1Department of Pharmaceutics, School of Pharmacy, University of Health and Allied Sciences, Ho, Ghana; 2Department of Pharmaceutical Sciences, University of Connecticut, Storrs, CT, USA; 3College of Pharmacy, Qatar University, Doha, QatarCorrespondence: Nashiru Billa, Department of Pharmaceutical Sciences, College of Pharmacy, QU Health, Qatar University, P.O Box 2713, Doha, Qatar, Tel +974 4403-5642, Email nbilla@qu.edu.qaAbstract: Oral administration of dosage forms is convenient and beneficial in several respects. Lipid nanoparticulate dosage forms have emerged as a useful carrier system in deploying low solubility drugs systemically, particularly class II, III, and IV drugs of the Biopharmaceutics Classification System. Like other nanoparticulate delivery systems, their low size-to-volume ratio facilitates uptake by phagocytosis. Lipid nanoparticles also provide scope for high drug loading and extended-release capability, ensuring diminished systemic side effects and improved pharmacokinetics. However, rapid gastrointestinal (GI) clearance of particulate delivery systems impedes efficient uptake across the mucosa. Mucoadhesion of dosage forms to the GI mucosa results in longer transit times due to interactions between the former and mucus. Delayed transit times facilitate transfer of the dosage form across the mucosa. In this regard, a balance between mucoadhesion and mucopenetration guarantees optimal systemic transfer. Furthermore, the interplay between GI anatomy and physiology is key to ensuring efficient systemic uptake. This review captures salient anatomical and physiological features of the GI tract and how these can be exploited for maximal systemic delivery of lipid nanoparticles. Materials used to impart mucoadhesion and examples of successful mucoadhesive lipid nanoformulations are highlighted in this review. Keywords: gastrointestinal, lipid nanoparticle, mucin, mucoadhesion, mucopenetration